Assessment of alcohol utilization during pregnancy and its associated factors among reproductive women in Mecha Woreda of North Western Ethiopia - Getaneh Bizuayehu Demeke; Eyayu Kasseye Bayu (BMC, 2022)
Abstract Background Pregnancy is a time when women are making many changes, including the patterns of alcohol consumption. Alcohol consumption during pregnancy encourages the risks of mothers and unborn child. Alcohol use during pregnancy can result in prematurity, brain damage, growth restriction, developmental delay and social, emotional and behavioral deficits, particularly in developing countries. Methods A community based cross-sectional study was employed. Structured questionnaires were used to assess the prevalence of alcohol utilization, and socio-demographic as well as economic characteristics of women who have pregnancy experience. Both bivariate and multivariate logistic regression models were employed. Descriptive and inferential statistical analyses were used. Results The study results showed that the prevalence of alcohol use and response rate was high. Factors like age group of women from 35-49 years (AOR = 0.221; 95%CI = 0.057-0.856), illiterate women(AOR = 2.697;95% CI = 1.207-6.026), currently pregnant (AOR = 0.139;95%CI = 0.057 0.343), women currently use alcohol (AOR = 0.021; 95% CI = 0.009 0.049), alcohol use pre-pregnancy (AOR = 0.016; 95% CI = 0.006-0.042), women drinking alcohol with husband during pregnancy (AOR = 0.228; 95% CI = 0.085-0.614), the risk of alcohol consumption during pregnancy is low(AOR = 0.262;95%CI = 0.074-0.925), risk alcohol consumption during pregnancy is medium (AOR = 0.296;95% CI = 0.103-0.849),utilization of alcohol during pregnancy is valuable (AOR = 0.104; 95%CI = .0.013-0.833) were statistically associated with alcohol use during pregnancy. Conclusion The result inferred that there is a high level of alcohol use throughout pregnancy. Due to the differences in the culture and communal means of drinking alcohol, the frequency of alcohol consumption during pregnancy varies among different regional studies and countries.